Strategi Marketing Public Relations dalam Membangun Hubungan Mitra Bisnis - Hersta Opiyalana; Rosita Anggraini (UNISBA Press, 2023)
Abstract. PT Tomo and Son has various products and services, one of which is training and education services which have stopped operating. PT Tomo and Son seeks to reactivate these services by implementing strategies that have been carried out, and continues to want to add and expand in building relationships with business partners. The purpose of this research is to find out the marketing public. and pass strategies. The concept used is a marketing public relations strategy. This study uses a qualitative research method with a descriptive type of research. The primary data collection technique was in-depth interviews with three informants, namely SS key informants, 1 MW informants and 2 RH informants. Secondary data is obtained from reference books, documents, and websites. Data analysis techniques through data reduction, data presentation and drawing conclusions. The results showed that PT Tomo and Son was successful in implementing a marketing public relations strategy in building relationships with business partners. The strategy is carried out using a pull strategy by bringing in clients directly, promoting using email blasts, flayers and social media, as well as sponsoring. Push strategy by maintaining good relations with clients and making it easy for new clients or clients to access information. Pass strategy by carrying out social activities such as being a regular donor at Islamic boarding schools, providing compensation for orphans, carrying out blood donations, collaborating with universities, as well as providing funds in every August 17 activity in the area around the company. PT Tomo and Son has succeeded in carrying out marketing public relations strategies so that it is able to build relationships with business partners in accordance with the targets to be achieved by the company. Abstrak. PT Tomo and Son memiliki bermacam produk dan jasa, salah satunya jasa training and education yang pernah berhenti beroperasi. PT Tomo and Son berupaya untuk mengaktifkan kembali jasa tersebut dengan menerapkan strategi yang pernah dilakukan, dan terus ingin menambah serta memperluas dalam membangun hubungan para mitra bisnis Tujuan penelitian ini adalah untuk mengetahui strategi marketing public.relations dalam membangun hubungan mitra bisnis dengan menggunakan pull, push dan pass strategy. Konsep yang digunakan adalah strategi marketing public relations. Penelitian ini menggunakan metode penelitian kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data primer adalah wawancara mendalam dengan tiga informan yaitu key informan SS, informan 1 MW dan informan 2 RH. Data sekunder didapat dari buku referensi, dokumen, dan website. Teknik analisis data melalui reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa PT Tomo and Son berhasil dalam menerapkan strategi marketing public relations dalam membangun hubungan dengan para mitra bisnis. Strategi yang dilakukan menggunakan pull strategy dengan cara mendatangkan langsung para klien, promosi menggunakan email blast, player dan media sosial, serta melakukan sponsorship. Push strategy dengan menjaga hubungan baik kepada para klien dan memberikan kemudahan untuk para klien atau klien baru dalam mengakses informasi. Pass strategy dengan melakukan kegiatan sosial seperti menjadi donatur tetap di pondok pesantren, memberi santunan untuk anak yatim, melaksanakan donor darah, bekerja sama dengan perguruan tinggi, serta pemberian dana dalam setiap kegiatan 17 Agustus di daerah sekitar perusahaan. PT Tomo and Son sudah berhasil dalam melakukan strategi-strategi marketing public relations sehingga mampu membangun hubungan dengan para mitra bisnis sesuai dengan target yang ingin dicapai Perusahaan.